Potential Economic and Development Prospects of Non Timber Forest Products in Community Agroforestry Land around Sibolangit Tourism Park - Affandi, Oding; Zaitunah, Anita; Batubara, Ridwanti (Forestry Faculty, Universitas Hasanuddin, 2017)
The communities who live around Sibolangit Tourism Park have developed nontimber forest products (NTFP) in their own agroforestry lands. This research evaluates the potential economic and development prospects from NTFP development in the Park by examining: (1) type of NTFP and economic value from community agrofrestry land, (2) contribution of NTFPs on household income, (3) development prospects of NTFP-based agroforestry around Sibolangit Tourism Park. The research was conducted in two selected villages around Sibolangit Tourism Park: Sembahe Village and Batu Mbelin Village. The research took place over a period between June and August 2016. Research data was obtained from in-depth interviews and observations. A descriptive method was used to analyze and describe facts related to the research aims. The type of NTFPs cultivated by communities at the research sites include mangosteen, durian, garcinia, candlenut, lanzones, lansium, bitter bean, and areca nut (as their forestry component) and ginger, turmeric, chili, papaya, etlingera, and banana (as the agriculture component). Most NTFPs are cultivated as a comercial product. The economic value of NTFPs in Batu Mbelin Village has reached Rp. 547,275,000/year or contribute 80.07% of total family income. Meanwhile, the economic value of NTFPs in Sembahe Village has reached Rp 682,100,000/year, contributing to 78.75% of total household income. Therefore, the prospects for supporting and expanding NTFP in agroforestry plots in and around Sibolangit Tourism Park has high potential for supporting household income